Sequential Shh expression in the development of the mouse upper functional incisor - Hovorakova, Maria; Smrckova, Lucie; Lesot, Herve; Lochovska, Katerina; Peterka, Miroslav; Peterkova, Renata (Journal of experimental zoology. Part B, Molecular and developmental evolution, 2013)
The mouse incisor is a frequently used model in studies of the molecular control of organ development. The appropriate interpretation of data on normogenesis is essential for understanding the data obtained in mutant mice. For this reason, we performed a very detailed investigation of the development of the upper incisor in wild-type mice from embryonic day (ED) 11.5 till 14.5. A combination of histology, whole mount in situ hybridization, computer-aided three-dimensional reconstructions, and fluorescent microscopy, has been used. Several sonic hedgehog (Shh) expression domains have been detected in the upper incisor region during early prenatal development. At ED11.5-13.5, there was a single Shh positive domain present in the anterior part of left or right upper jaw arches, corresponding to the epithelial thickening. More posteriorly, a new Shh expression domain appeared in the incisor bud in the developmentally more advanced ED13.5 embryos. At ED14.5, only this posterior Shh expression in the incisor germ remained detectable. This study brings new insights into the early development of the upper incisor in mice and completes the data on normal mouse incisor development. The temporal-spatial pattern of Shh expression reflects the development of two tooth generations, being detectable in two successive, antero-posteriorly located areas in the prospective incisor region in the upper jaw. The first, anterior and superficial Shh expression domain reflects the rudimentary tooth development suppressed during evolution. Only the subsequent, posterior and deeper Shh expression region, appearing at ED13.5, correlates with the prospective upper functional incisor in wild-type mice.
Keywords: Maxilla; hybridizace in situ; Hedgehog Proteins; vývojová regulace genové exprese; Incisor; Odontogenesis; fylogeneze; fluorescenční mikroskopie; Gene Expression Regulation, Developmental; Phylogeny; In Situ Hybridization; řezáky; Animals; Microscopy, Fluorescence; proteiny hedgehog; myši transgenní; odontogeneze; zvířata; maxila; myši; Mice; Mice, Transgenic